Dollarization of Liabilities : Beyond the Usual Suspects - Barajas, Adolfo (IMF Working Papers; Working Paper ;, 2003)
Dollarization of liabilities (DL) has emerged as a key factor in explaining the vulnerability of emerging markets to financial and currency crises. "Usual suspects" of causing DL comprise "fatalistic" determinants such as a long history of unsound macroeconomic policies and development and institutional factors, aided by moral hazard opportunities related to government guarantees. This paper assesses empirically the relevance of these factors relative to alternative explanations. Based on a sample of Latin American countries, we find that ongoing central bank intervention in the foreign exchange market, relative market power of borrowers, and financial penetration are at least as important in explaining DL.